Knowledge Transfer through Mobile Application Needs Questionnaire: Validity and Reliability - Melati Fajarini; Sri Rahayu (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2020)
Introduction: Knowledge transfer through mobile application needs assessment to develop a user-friendly technology. However, the means to measure the need is unavailable. An instrument was developed from the Joanna Briggs new model of EBP to examine the nurses’ needs. This study aims to examine the reliability and validity of knowledge transfer through mobile application needs questionnaire for nurses. Methods: The validity of the questionnaire was examined for its content with Content Validity Index (CVI). CVI was measured for its relevance, ambiguity, clarity and simplicity on each item (I-CVI) and scale (S-CVI). Content validity assessment forms and guidelines were given to six experts in nursing and computer sciences. Their suggestions contributed to the questionnaire revision. Subsequently, the online questionnaire was completed by 40 nurses randomly selected in a hospital in Depok City. Internal consistency was analyzed for the reliability. Results: The CVI of this questionnaire is high with mean of I-CVI and S-CVI at 0.96 relevance, 0.98 ambiguity, 0.97 clarity and 0.94 simplicity. Cronbach’s alpha shows that the internal consistency is acceptable (0.87). Conclusion: The questionnaire is content valid and reliable. This questionnaire can be used to measure those needs and contribute to the design of a user-friendly mobile application.